Monitoring of sport participation and injury risk in young athletes - Malisoux, L.; Frisch, A.; Urhausen, A.; Seil, R.; Theisen, D. (Journal of Science and Medicine in Sport, 2013)
Objectives: Careful modulation of training characteristics in high-level sports optimizes performance and avoids inappropriate workloads and associated sports injury risk. The aims of this study were to compare sport participation characteristics in different youth sport categories and to investigate their relationship with injury. Design: Prospective cohort follow-up. Methods: Young (12-19 years) high-level athletes (n = 154) from a regional sport school were followed during 41 weeks regarding sport participation characteristics and traumatic and overuse sports injuries (time-loss definition). All data were self-recorded by the athletes in an electronic system "TIPPS" (Training and Injury Prevention Platform for Sports) and subject to a systematic data quality control. Volume and intensity (self-rated perceived exertion) of each sport session were used to compute weekly load, monotony and strain. Sport categories were defined as team, racket, and individual sports. Results: All sport participation characteristics were dependent on sport category (p < 0.05). Weekly intensity, load and strain were dependent on age (p < 0.05). Racket and individual sports were associated with lower injury risk (HR = 0.37 and 0.34, p = 0.001 and p < 0.001, respectively) compared to team sports. Average sport participation characteristics were not related to injury according to the survival analysis. However, intensity during the week prior to injury was significantly higher (p < 0.01) compared to that of the 4 preceding weeks. Conclusions: This study investigated for the first time the relationship between sport participation pattern and injury risk in young athletes. The monitoring method was sensitive to variations according to pertinent variables and might help identify athletes with increased sports injury risk.